Peningkatan Kompetensi “Listening” Berbentuk Transaksional dan Interpersonal Melalui Pendekatan Genre Text (Recount) Siswa Kelas X - Andayani, Endah Alamsari; Riza, Moch Dicky (Jurnal Ilmiah Wahana Pendidikan, 2023)
High school English instruction aims to prepare students for college by helping them attain the functional level, which involves speaking and writing to address everyday issues, and the informational level, which involves becoming proficient in the language..This is indeed listening comprehension, but it needs to be preceded by simple listening related to classroom management which will later make the learning process run well. Story telling activities usually attract students, especially if the teacher can bring stories well.To do teaching with audio video, we don`t necessarily have to use a language laboratory. Following the preparation of the lesson plan, the following instructional techniques can be applied to enhance the interactive and engaging environment in the classroom.This teaching strategy can not only be done in the classroom in teaching and learning activities, but can also be applied in student study groups outside school hours.